Cotistas negros da UFSM e o mundo do trabalho - Dutra, Maria Rita Py (2018)
The current PhD research, from the Post-Graduation Program in Education of the Federal University of Santa Maria – UFSM had as leading question “in which measure to ingress as a black quota holder student in Affirmative Actions of Social and Racial Inclusion Program of UFSM, during the period of 2008 to 2015, interfered on the insertion in the labor market, of these students, after their graduation?”. The general objective was to understand the challenges faced by black quota holder students graduated at UFSM to the insertion in the labor market. The specific objectives were: to rescue the trajectory of implantation of quota politics at UFSM, to evaluate how the formal process of accessing the labor market in their respective areas of formation, i.e. students who concluded Social Sciences and in the other most and least pursued courses on the entrance exam from that period, to enumerate the difficulties found by the quota holder black student during his/her course and what they have done to surpass them in order to access the labor market; to analyze how much the social or influenced on the access in the labor market; identify in which moment and how occurred the formal process of accessing the labor market by the graduate student and how the quotes changed their lives. The collaborators were 11 quota holder black students (4 men and 7 women), from the courses of Nursery, Special Education, Social Service, Sociology, Public Relations, Veterinary, Social Sciences (3), History and Physiotherapy from UFSM. The methodology used was a qualitative approach; and semi-directed and open interviews, online questionnaires, documental research, observation of the participant and life-story were carried out. Among the theorists who were taken as a basis to the research, there is Bordieu (1997a; 2008a; 2008b), a reference about the cultural capital and the school as a reproducer of social inequality; the masterful study by Coulon (2008), with the indications about the conditions of the new students into higher education. The category labor was revisited from the theoretical framework provided by Durkheim (2010), Marx (2015) and Weber (1967). On the studies of Freire (1987), it was sought for the analysis of the educational field, and on the ones provided by Domingues (2008), Gomes (2001), Gomes (2003), Martins (2014), Munanga (2009), Santos (2015) and Valentim (2012) considerations about affirmative actions, quota policies and studies in which the collaborators were quota holder black students. The results obtained indicated that from 2008 to 2015, 2004 quota holder black students (black, brown) have entered at UFSM, 254 had graduated, corresponding to 11,52% of the ethnical quota holder students and 3,25% of the total number of graduations. The situation of the collaborators, after their graduation, was defined in such way: the nurse and the social assistant accessed the labor work by public context; the sociologist, after curriculum analysis, and the physiotherapist, after the indication of a former professor. It was highlighted that most of the collaborators opted by continuing the studies (9), investing in the academic field: 2 asked for reentrance, 3 were taking specialization courses; 1 was taking a master‟s degree and 3 were taking a doctored one. For them, the quotes policy represented a game changer, changing totally their lives, it was like a door that open to the worldwide. Publicizing from the rooftops that they were ethnical quota holder students was a desire expressed by the collaborators, who are proud of their quota holder condition, because nowadays they recognize a more democratic and more diverse university, in the pursuit of social justice, a “university that color itself with people”. This research intends to be only a starting point and it is pointed out the necessity of studying, developing, debating and researching topics as “decolonization; who is black in Brazil, whiteness, white privileges, colorism, cultural appropriation, racism”, among others. The final considerations of this study will be sent to the competent organs from the University, such as the Rector‟s Office, the Office of Students Affairs; the Office of Graduating Studies, the Coordination of Educative Actions -CAED, the Nucleus of Social Affirmative, Ethnical-Racial and Indigenous Actions, NEAB, DCE and associations of servers and professors, as ASSUFSM and SEDUFSM, and by informing such results I hope to be contributing to the improvement of the quota policies at UFSM.